Support for compassionate care: Quantitative and qualitative evaluation of Schwartz Center Rounds in an acute general hospital. (June 2016) - Chadwick, Raymond J; Muncer, Steven J; Hannon, Bronagh C; Goodrich, Joanna; Cornwell, Jocelyn
Objective: To evaluate the impact of Schwartz Center Rounds, a multi-disciplinary forum to reflect on the emotional consequences of working in healthcare, on the staff of a large acute general hospital over a three-year period. Design: Evaluation data following each Round were collected routinely from all staff attending over this period and analysed quantitatively and qualitatively. Setting: An integrated university teaching trust with both acute hospital and community services in the North East of England. Participants: Over the three-year period of the study, 795 participant evaluation forms were returned by staff attending the Rounds. Main outcome measures: A standard evaluation form completed at the end of each Round by those present, including ratings on a five-point scale against each of eight statements and an opportunity to offer additional free text comments. Results: The findings show a very positive response to all aspects of the Rounds by staff who attended. The most highly rated statement was: 'I have gained insight into how others think/feel in caring for patients'. This was reinforced by the qualitative analysis in which the primary theme was found to be Insight. There were no significant differences between disciplines/staff groups, indicating that all staff whether clinical or non-clinical responded to the Rounds equally positively. Conclusions: Schwartz Rounds are highly valued by staff from all disciplines, and by managers and other non-clinicians as well as clinicians. They appear to have the potential to increase understanding between different staff, and so to reduce isolation and provide support.